Traditional American values expressed in gone with the wind movie and decoding of its success - Lê, Thị Linh (2020)
This study aims at investigating the traditional American values expressed in Gone with the Wind movie and decoding of its success. The method of direct observation and documentary analysis will be intensively used in this research. Specifically, in chapter III, the research will directly observe the movie in order to analyze the content and explore the traditional American values in the Gone with the Wind movie. In chapter IV, the researcher will carefully study and analyze a wide range of sources, such as film reviews and critics, websites, online and printed newspapers and journals, and published books in order to find out the factors leading to the movie’s success. In the thesis, chapter one and two gives the background knowledge of the thesis. Particularly, it provides the readers with the notion of traditional American values as well as the necessary information of Gone with the Wind movie. In chapter III, after direct observation, the researcher has found out six traditional values implicit in Gone with the Wind movie, which correspond to the ones mentioned in chapter II. In chapter VI, the researcher discovered the reasons leading to the movie’s success within the limit of American Study. There are a number of factors resulting in the achievement of Gone with the Wind, in which traditional American values plays an important role.